PENERAPAN TERAPI GESTALT DALAM PENGELOLAAN EMOSIONAL YANG TERPENDAM PASIEN SKIZOFRENIA PARANOID “SW” DI RUMAH SAKIT JIWA Dr. H. MARZOEKI MAHDI KOTA BOGOR - Rajabi, Muhammad Ibadillah; Utami, Nazera nur (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Schizophrenia based on DSM-V defines it as a mental disorder characterized by psychotic symptoms that last for at least six months. Where reality and thought patterns cannot be in line. This community service aims to explore the application of gestalt therapy using the Nourisment Technique in emotional management in client "SW" diagnosed with paranoid schizophrenia at Dr. H. Marzoeki Mahdi Hospital, Bogor City. Client "SW" is a 47-year-old man who has experienced positive symptoms of Paranoid Schizophrenia since 2021-2024, client "SW" has symptoms of problems, namely difficulty expressing pent-up emotions. The method in community service, the method used is case work. The data collection techniques used were observation, documentation studies and in-depth interviews, and the results obtained after the gestalt therapy intervention using the nourishment technique included: 1. Client "SW" can express emotions through coloring and writing media, 2. Client "SW" can express everyday feelings by telling stories to family, 3. Client "SW" can control his emotions well.